(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The main causative agents of parenteral infections are human immunodeficiency viruses, hepatitis B and C viruses. The impossibility of replacing blood with synthetic components and parenteral infections determines the relevance of increasing the safety of blood transfusion